Analisis Makna Metafora Pada Lirik Lagu Nadin Amizah â€œSorak Soraiâ€ - Nurashri Shafary (Madani: Jurnal Ilmiah Multidisiplin, 2023)
One way to express feelings is to write them into a song lyric that is full of meaning. Nadin Amizah created the song "Sorak Sorai" which tells the story of a 'beautiful farewell.' This study discusses the types of metaphors and meanings contained in the lyrics of the song "Sorak Sorai" by Nadin Amizah. The purpose of this study was to describe the types of metaphors and meanings contained in the lyrics of Nadin Amizah's song "Sorak Sorai." The method used is descriptive qualitative method. The data used is sourced from the lyrics of Nadin Amizah's song, entitled "Sorak Sorai." The results of this study are obtained 5 lyrics that use anthropomorphic metaphors (anthropormic metaphors), 3 lyrics that use metaphors from concrete to abstract (from concert to abstract), 8 lyrics that use synesthetic metaphors (synesthetic metaphors), and no lyrics that use metaphors. animality (animal metaphor).